Kinerja Jaringan Irigasi Air Tanah pada Irigasi Hemat Air Berbasis Pompa Air Tenaga Surya - Joubert, Marasi Deon; Ridwan, Dadang; Pratiwi, Ratna Manik (Balai Teknik Irigasi, 2016)
Groundwater Irrigation Network (JIAT) contributes substantially to agricultural production especially in the dry season. Limited water availability needs to be handled by water-efficient irrigation methods. JIAT which is built in Ponorogo has not been optimally utilized yet. So, it needs to be revitalized using both drip irrigation and solar energy system to operate the submersible pump. This study uses 51 solar panels covering area of 120 m2. Evaluation resuts of the technology application shows that solar energy can generate 7,873.5 watts, maximum discharge 14.17 liter/second, average CO2 emission reduction 4.1 kg/day, 96.51% irrigation uniformity, drip uniformity of 97.72% and emitter rate of 3.99 mm/hr. CO2 emission can be reduced until 1.29 tons for one pump operation on 10 consecutive months. Moreover, potential reduction of CO2 will reach 4.506 tons in a year if 50% of JIAT pumps from 7,000 existing pumps can be converted to be solar-based pumps. Water productivity for the cultivation of watermelon plants can be achieved as 35.63 kg/m3 water. The water-use efficiency is 60% - 92% compared to the similar research. In addition, pump-operation costs can be decreased to 94.92% compared to the cost of diesel-fueled pump.Â